Sosialisasi Bullying dan Upaya Penanganannya Kepada Guru dan Siswa di SDN 69 Kendari - Wa Ode Lili Andriani Nasri; Alber Tigor Afriyanto; Nana Sumarna; Dodi Priyatmo Silondae; Erma Pratiwi Nufi; Ordiman Lasaima (Indo Publishing, 2025)
Bullying is a crucial problem in today's education world, from elementary to college, so it is important to continue to hold socialization as a form of preventive action. This Community Service activity aims to provide knowledge and understanding to teachers and students about bullying. The implementation of this activity was attended by 30 students and 2 teachers at SDN 69 Kendari. The material given to participants includes the definition, factors that influence and impacts and handling efforts that can be done by the school in preventing and eradicating bullying behavior. The results obtained by students were enthusiastic about this activity because it was something new, on the other hand the school represented by the teacher gave appreciation related to this activity because it got a real picture of Bullying and how the school should respond to this behavior.